ANALISIS PERAN PELATIHAN DALAM MENINGKATKAN PRESTASI KERJA KARYAWAN PADA PERUSAHAAN BATA RINGAN JAYABRIX LAMONGAN - Ahmad Yani Syaikhudin; Ahmad Fathur Rozi (J-MACC, 2019)
Today the industry is growing and developing rapidly in various places. The purpose of establishing these industries is inseparable from the objectives to be achieved by the company. These objectives include to obtain large profits with minimal production costs. The "Jayabrix Indonesia" Lightweight BrickCompany in Paciran Lamongan is one of the national private companies engaged in the production of several Lightweight Brick.For this company to achieve the above goals and maintain consumer confidence is not an easy thing. The existence of very tight market competition will force the company to be able to implement a good strategy in an effort to achieve the above goals. From observations, interviews, and joint observations with employees of the Lightweight Brick company "Jayabix" in Lamongan, the authors found a problem where the main cause of low employee performance is because they are less capable and less able and less skilled at work so the way they work is less effective and not efficient which ultimately affects the productivity of the company. This is what the writer will try to improve employee work performance so that the productivity of the company goes well, one of them is by using research methods. After carrying out data analysis, it can be seen that the correlation coefficient (r) is 0.708 and the determination coefficient is 50,3%, meaning that training has an important role in employee performance, then after the hypothesis testing is known, t count itung t table is 9,214 > 2,358. shows a strong role between training and employee performance.